Wall-free droplet microfluidics for probing biological processes by high-brilliance X-ray scattering techniques - Marinaro, G.; Graceffa, R.; Riekel, C. (Frontiers in Molecular Biosciences, 2022)
Here we review digital microfluidics applications based on droplets deposited on inert or reactive surfaces by inkjet or related devices. One of the main interests for probing droplets by X-rays generated by high brilliance Synchrotron Radiation or X-Ray Free Electron Laser sources is a reduction in sample consumption as compared to continuous flow microfluidics, allowing studying small quantities of biological matter or probing structural processes in small volumes. In contrast to continuous flow microfluidics, droplets evaporating in air allow also increasing molecular solution concentration up to residue formation such as amyloid fibrillation. Droplets on superhydrophobic surfaces come close to wall-free confinements and can serve as micro-reactors for probing structural transformations during evaporation and droplet coalescence, including chemical reactions. We review basics of droplets printing, printing technology and practical experience at a synchrotron radiation beamline optimized for nano-/microbeam small- and wide-angle X-ray scattering. Simulations of flow fields in evaporating sessile droplets and their volume dependence are reported. Selected droplet applications with biological relevance are reviewed and perspectives for the use of droplet generating devices at ultra-brilliant light sources are discussed.